P16 Past smoking does not influence response to biologic therapy in patients with severe asthma. (11th November 2022) - Rahman, M; Dennison, P; Azim, A; Freeman, A; Haitchi, HM; Kurukulaaratchy, R; Rupani, H
Abstract : Background: Many patients with severe asthma (SA) have a smoking history. Clinical trials for asthma biologics/monoclonal antibodies excluded current smokers (CS) and ex-smokers (ES) with a significant smoking history. The effect of past smoking on biologic outcome in asthma is unclear. Aims: To determine whether smoking history impacts biologic therapy response in SA. Methods: SA patients started on omalizumab (n=101), mepolizumab (n=93) and benralizumab (n=50) before 2021 were retrospectively reviewed. ES were split into <20 pack years (PY) and ≥20PY. A positive response to biologic was defined as >50% reduction in exacerbations needing oral steroids or maintenance steroid dose at 12 months, or, for omalizumab clinical improvement at 4 months. All patients were from a single centre. Results: Of 252 patients, 134 were NS (53%), 72 ES with <20PY (29%), 38 ES with ≥20PY (15%) and 8 CS (3%). 96/110 (87%) had stopped smoking >5 years ago. Past smoking did not affect response to biologic: positive response in 113/134 (84%) NS, 62/72 (86%) ES <20PY and 28/38 (74%) ES ≥20PY. Asthma Control Questionnaire (ACQ) score improved significantly with biologic therapy in NS (2.5 to 1.6, p<0.0001), ES <20PY (2.8 to 2.0, p=0.0008) and ES ≥20PY (2.8 to 2.0, p=0.02) and there was no clinical or statistical difference in 12-month ACQ between the 3 groups. ES with ≥20PY (but not ES with <20PY) had worse lung function compared to NS (post-bronchodilator FEV1/FVC 68% NS, 66% ES <20PY, 56% ES ≥20PY, p=0.0017). Numbers of CS were low but significantly fewer had a positive response to biologic: 2/8 (25%, p=0.002). Conclusion: Almost 50% of SA patients on biologics in our centre had a smoking history. Past smoking history did not impact clinical response to biologics in patients with SA.